2014
DOI: 10.1155/2014/209548
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Platelet Concentrate: Titanium-Prepared Platelet-Rich Fibrin

Abstract: We developed a new product called titanium-prepared platelet-rich fibrin (T-PRF). The T-PRF method is based on the hypothesis that titanium may be more effective in activating platelets than the silica activators used with glass tubes in Chouckroun's leukocyte- and platelet-rich fibrin (L-PRF) method. In this study, we aimed to define the structural characteristics of T-PRF and compare it with L-PRF. Blood samples were collected from 10 healthy male volunteers. The blood samples were drawn using a syringe. Nin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
80
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(108 citation statements)
references
References 22 publications
2
80
0
1
Order By: Relevance
“…TPRF tries to overcome this disadvantage by using the titanium tubes for activating the clot. In their initial trials, Tunali et al . found that, although titanium induced platelet aggregation similar to that in glass tubes, and the clot produced in the titanium was clinically identical to that produced in the glass tubes, the activation of platelets with titanium induces distinctive characteristics of TPRF, including its increased biocompatibility.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TPRF tries to overcome this disadvantage by using the titanium tubes for activating the clot. In their initial trials, Tunali et al . found that, although titanium induced platelet aggregation similar to that in glass tubes, and the clot produced in the titanium was clinically identical to that produced in the glass tubes, the activation of platelets with titanium induces distinctive characteristics of TPRF, including its increased biocompatibility.…”
Section: Discussionmentioning
confidence: 99%
“…Titanium is a unique material in itself, having the highest weight to strength ratio and corrosion resistance compared to other materials. This improves the hemocompatability of the material, which further facilitates the formation of a more polymerized fibrin network …”
Section: Introductionmentioning
confidence: 99%
“…OFD is a procedure for horizontal bone loss due to periodontitis; however, recurrence of pathologic pockets and postoperative GR can be observed after surgery when OFD is used alone. PRF is an autogenic and very inexpensive biologic material for which the literature is growing, and recent studies 34 , 49 , 50 have tended to develop novel techniques to improve physical (resorption time) and biochemical (growth factor contents) properties of PRF products. Therefore, the clinical significance of periodontal parameters may be improved with use of novel forms of PRF.…”
Section: Discussionmentioning
confidence: 99%
“…To obtain PRF, 20 mL venous blood was drawn by syringe from the antecubital vein of patients and immediately transferred to two sterile tubes (10 mL each) and centrifuged at 2,800 rpm for 12 minutes, according to the protocol developed by Tunalı et al 34 After centrifugation, PRF clots were removed from the tubes using sterile tweezers, separated from the red corpuscle base (preserving a small red‐blood‐cell layer) using scissors, and placed on sterile woven gauze to release their serum slowly for 20 minutes. Two stable fibrin membranes were obtained by squeezing serum out of the PRF clot.…”
Section: Methodsmentioning
confidence: 99%
“…The T-PRF exhibited an organized and high integration architecture in comparison with L-PRF, and the histomorphometric results showed a thicker and larger area of fibrin networks in T-PRF than in L-PRF. [69] Although their case report was focused on periodontal furcation recession, Sambhav et al described promising future perspectives for regenerative peri-implants for the purpose of soft and hard tissue defects. Their case showed that the treatment of an advanced (Grade II) buccal furcation area with the use of PRF in combination with β-tricalcium phosphate (β-TCP) and a simple pedicle flap can enhance root coverage.…”
Section: Current Directions Regarding the Additive Effectsmentioning
confidence: 99%